2021
DOI: 10.1002/jcp.30313
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunological insights into the pathogenesis of ankylosing spondylitis

Abstract: Ankylosing spondylitis (AS) is inflammatory arthritis predominantly affecting the spine, which is involved in the disorders of both immune and skeletal systems. The exact pathogenesis of AS is not fully understood. Osteoimmunology is a new subject of study in inflammatory arthritis, in particular the pathogenic events involved in the crossregulation of both skeletal and immune systems. In this review, we discuss osteoimmunological and pathological changes of AS in the spine that are characterized by altered os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 131 publications
0
30
0
Order By: Relevance
“…(2) CDC42 regulates the differentiation of the osteoclasts and osteoblasts, further maintain the function of bone modeling and remodeling. Thus, the downregulation of CDC42 might be correlated with the initiation of the AS 30‐33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) CDC42 regulates the differentiation of the osteoclasts and osteoblasts, further maintain the function of bone modeling and remodeling. Thus, the downregulation of CDC42 might be correlated with the initiation of the AS 30‐33 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the downregulation of CDC42 might be correlated with the initiation of the AS. 30 , 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…The pathological changes and osteoimmunological features of AS mainly include osteolytic bone destruction and osteogenic changes. The interaction of T cells, B cells, osteoblasts, and osteoclasts together regulate the pathogenesis of AS ( 6 ). More importantly, the long course of AS as a chronic inflammatory disease makes the emotional and financial devastation of the patient unbearable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of bone erosion and bone formation in AS is not completely understood 5 . In recent years, many studies have reported that cytokines play a vital role in disease pathology, 6‐9 and other studies have reported that the dysregulation of the immune system and bone metabolism may play a critical role in AS etiology 10,11 …”
Section: Introductionmentioning
confidence: 99%